Nature at risk - Harlow, Rosie; Morgan, Sally (Kingfisher London, 1999)
Focuses on the world of nature and how it is under threat by humans, discusses how we can preserve and protect wildlife and its natural resources. Includes experiments and activities. Suggested level: primary, intermediate